MANUSIA DAN LINGKUNGAN HIDUP DALAM AL-QUR'AN - Miskahuddin, Miskahuddin (Forum Intelektual Qur'an dan Hadits Asia Tenggara (SEARFIQH) Kota Banda Aceh, 2019)
Humans are intelligent beings that God has given him the ability to think and the ability to do his work according to what is planned and thought. Sometimes the ability to think of humans is not in accordance with anything they want to do. It is often in conflict between the desires of the passions and his common sense to do something, so that it can bring about the results of his work harming himself and his environment. To overcome social problems directed at environmental destruction, the Qur'an is the only guideline of human life that is able to overcome various social problems including the actions of environmental destruction by humans. In accordance with the guidance and direction of the Qur'an as a holy book and guidance for believers and all people in the world, the Qur'an tells humanity to always preserve the environment and strongly prohibits it when humans do environmental destruction live on this earth, because God does not like the perpetrators of destruction. Balance and preservation of the environment is the teachings of Islam that must be obeyed and obeyed in a pure and consistent manner in accordance with the guidance of the Qur'an and Al-Hadith, especially for Muslims who believe and are devoted to Allah S.W.T.